2008
DOI: 10.1016/j.neulet.2008.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells abrogate experimental allergic encephalomyelitis after intraperitoneal injection, and with sparse CNS infiltration

Abstract: Multiple sclerosis is a currently incurable inflammatory demyelinating syndrome. Recent reports suggest that bone marrow derived mesenchymal stem cells may have therapeutic potential in experimental models of demyelinating disease, but various alternative mechanisms, ranging from systemic immune effects to local cell replacement, have been proposed. Here we used intraperitoneal delivery of human mesenchymal stem cells to help test (a) whether human cells can indeed suppress disease, and (b) whether CNS infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 18 publications
4
65
0
3
Order By: Relevance
“…67 Several other studies confirmed the beneficial effect of MSCs injected systemically, 33,68 i.p. 69 or locally inside the CNS, 68 suggesting that not only do MSCs exert a potent inhibition of the autoimmune attack to the CNS but are also endowed with significant neuroprotective effects despite limited evidence of CNS infiltration (Figure 2). 16 It is noteworthy that neural stem cells 70 and, more recently, human embryonal stem cellderived neuronal precursor cells, 71 displayed a strikingly beneficial effect upon administration in EAE-affected mice through bystander mechanisms leading to the immunomodulation of autoreactivity and neuroprotection.…”
Section: Animal Models Of Autoimmunitymentioning
confidence: 99%
“…67 Several other studies confirmed the beneficial effect of MSCs injected systemically, 33,68 i.p. 69 or locally inside the CNS, 68 suggesting that not only do MSCs exert a potent inhibition of the autoimmune attack to the CNS but are also endowed with significant neuroprotective effects despite limited evidence of CNS infiltration (Figure 2). 16 It is noteworthy that neural stem cells 70 and, more recently, human embryonal stem cellderived neuronal precursor cells, 71 displayed a strikingly beneficial effect upon administration in EAE-affected mice through bystander mechanisms leading to the immunomodulation of autoreactivity and neuroprotection.…”
Section: Animal Models Of Autoimmunitymentioning
confidence: 99%
“…For example, MSC derived from adipose tissues or bone marrow have been used to treat experimental allergic encephalitis, inflammatory bowel disease, immune-mediated arthritis, airway inflammation, and graft-versus-host disease in rodent models [1,[9][10][11][12]. In addition, human MSC have been administered to rodent models of inflammatory diseases [13][14][15][16][17]. Thus, it is apparent that the immune modulatory properties of MSC can be utilized therapeutically in a number of different diseases settings.…”
Section: Introductionmentioning
confidence: 99%
“…Gordon et al [39] used intra-peritoneal infusion of the hMSC to evaluate whether the CNS engraftment is a significant concern for treatment. They demonstrated an extensive improvement of clinical symptoms in EAE mice with little CNS infiltration.…”
Section: The Immune Effects Of Mscmentioning
confidence: 99%